Eksplorasi Pengalaman Bidan dalam Edukasi Deteksi Dini Perkembangan Bahasa Anak di Wilayah Pesisir: Studi Kasus Kualitatif - Renny Adelia Br Tarigan; Nuzulia Irawati; Rizanda Machmud; Eva Chundrayetti (Jurnal Ners, 2026)
Background: Early detection of language development disorders is essential to prevent long-term developmental delays in children. In coastal areas with limited resources, midwives play a crucial role as frontline healthcare providers in educating parents. This study aimed to explore midwives’ experiences in delivering education on early language development detection. Methods: This study employed a qualitative case study design conducted in coastal areas. Two midwives were selected as key informants based on their professional experience in maternal and child health services. Data were collected through in-depth interviews and analyzed using thematic analysis. Ethical approval was obtained, and informed consent was secured. Results: Three main themes emerged: (1) limited parental understanding of language development milestones, (2) barriers in delivering effective education, and (3) constraints related to healthcare services and geographical accessibility. Cultural beliefs and low awareness were identified as key factors influencing parental responses. Conclusion: Midwives play a critical role in early detection; however, multiple barriers hinder effective implementation. Strengthening communication strategies and improving service support are necessary to enhance early detection practices in coastal settings.